2011
DOI: 10.1124/jpet.111.182774
|View full text |Cite
|
Sign up to set email alerts
|

Afobazole Modulates Neuronal Response to Ischemia and Acidosis via Activation of σ-1 Receptors

Abstract: Afobazole is an anxiolytic medication that has been previously shown to be neuroprotective both in vitro and in vivo. However, the mechanism(s) by which afobazole can enhance neuronal survival remain poorly understood. Experiments were carried out to determine whether afobazole can decrease intracellular calcium overload associated with ischemia and acidosis and whether the effects of afobazole are mediated via interaction of the compound with receptors. Fluorometric Ca 2ϩ imaging was used to resolve how appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…Incubation in the s-1-receptor antagonist BD-1047 reduced the effects of afobazole by ∼40%. The concentration and degree of block reported here is consistent with previous studies showing BD-1047 inhibition of s-1-receptor-mediated effects in cortical neurons and retinal ganglion cells (Katnik et al, 2006, Cuevas et al, 2011a, Mueller et al, 2013. The lack of involvement of s-2 receptors is confirmed by results obtained using the s-2 receptor antagonist rimcazole .…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Incubation in the s-1-receptor antagonist BD-1047 reduced the effects of afobazole by ∼40%. The concentration and degree of block reported here is consistent with previous studies showing BD-1047 inhibition of s-1-receptor-mediated effects in cortical neurons and retinal ganglion cells (Katnik et al, 2006, Cuevas et al, 2011a, Mueller et al, 2013. The lack of involvement of s-2 receptors is confirmed by results obtained using the s-2 receptor antagonist rimcazole .…”
supporting
confidence: 81%
“…Unlike ANAVEX2-73, afobazole does not interact with muscarinic receptors (Seredenin and Voronin, 2009). Activation of s-1 receptors by afobazole results in a decrease in ischemia-induced Ca 21 overload, which is due in part to inhibition of NMDA channel activation (Katnik et al, 2006, Cuevas et al, 2011a. Previous studies have suggested other mechanisms for the neuroprotective properties of afobazole, including decreased caspase-3 activation and reduced oxidative stress (Zenina et al, 2005, Antipova et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that activation of s receptors inhibit acidosis-evoked [Ca 21 ] i overload (Herrera et al, 2008;Cuevas et al, 2011a). Experiments were conducted to determine whether migration or removal of the methyl moiety would alter the ability of the o-DTG derivatives to inhibit acidevoked elevations in [Ca 21 ] i .…”
Section: Resultsmentioning
confidence: 99%
“…Кроме того, проникновение фабомо-тизола через гематоэнцефалический барь-ер, где активно функционирует данный транспортер, будет достаточным для дос-тижения минимальной терапевтической концентрации в ткани мозга, даже несмот-ря на его индукцию в условиях дефицита кислорода [6,10]. Это подтверждается ре-зультатами многочисленных исследований эффективности фабомотиазола в качестве анксиолитика и нейропротектора [13,14]. Вывод В эксперименте in vivo на кроликах породы Шиншилла установлено, что фа-бомотизол не является субстратом белка-транспортера гликопротеина-P. …”
Section: исходные значения N=6unclassified